مقایسه عملکرد حافظه در جانبازان دارای عالئم اختالل استرس پس از سانحه با گروه بدون اختالل. - علیرضاپیرخائفی (Qom University of Medical Sciences Journal, 2022)
Background and Objectives The physical and mental health of war veterans depends on paying attention to their psychological problems. This study aims to compare the memory performance of disabled Iranian veterans with and without post-traumatic stress disorder (PTSD). Methods This is a retrospective cohort study conducted in 2016-2017. Participants were 30 veterans with PTSD and 30 veterans without this disorder in Iran who had records in the Foundation of Martyr and Veterans Affair. The diagnosis of PTSD or its absence was previously made by a psychiatrist and approved by the medical commission of the Foundation of Martyr and Veteran Affairs. The sampling method was done using a purposive method and was done based on the inclusion criteria. The data collection tool was the Wechsler memory scale (WMS). Data analysis was performed using multivariate analysis of variance. Results There was a significant difference between the two groups in all WMS subscales (general information, orientation, mental control, logical memory, digit span, visual memory, associate learning). Conclusion Memory performance of disabled Iranian veterans with and without PTSD is different in all dimensions.